A formação continuada do coordenador pedagógico e o trabalho de formação junto aos professores especialistas - Monteiro, Leonardo (Universidade Federal de São Carlos, 2019)
This study has as main goal to comprehend the possibilities regarding the multidisciplinary training of the pedagogical coordinator and how this training process can contrib the work of a specialist teacher. For this purpose, we are going to use as a resource the context of a specific pedagogical coordinator training program developed by a private non-profit organization of schools in the State of São Paulo, Brazil. For the research proposal, the following specific objectives were defined: to describe and analyze the institutional aspect of a specific program of multidisciplinary training of pedagogical coordinators, to identify the difficulties and possibilities of the pedagogical coordinator trainer, to understand the pedagogical coordinators' perceptions about their continued education and their training practices with the specialist teachers. The research has a qualitative nature, of the interpretative type, and used documents of the research program, mixed questionnaires with coordinators and coordinators trainers who were analyzed by questions (open and closed), with subsequent intercrossing of data and an interview with the woman who idealized the program. For the analysis of data, the ‘data triangulation’ technique and theoretical assumptions were used in relation to the continued training of the pedagogical coordinator, based in the contributions of Canário (2001) about the school-centered training, identity development of the coordinator, Placco (2011), André and Vieira (2002), perception of the school as a learning organization, Fullan e Hargreaves (2000), issues of knowledge, Tardif and Lessard (2002, 2004 and 2005), continued education, by Nóvoa (1988, 1999), Gatti and Barretos (2009), Libâneo (2004, 2007, 2012 and 2015), investigative stance, Cochran-Smith, Liytle (1999). The results indicate that the pedagogical coordinators and trainers of these coordinators consider that the multidisciplinary training program is an important training space for the development of the work with the specialist teacher and it potentiates the teacher training, but the program could foresee more moments of the trainer together with the coordinators in the school unit, in addition, the coordinator trainers expected that the program would provide more training to strengthen their work with the coordinators. It was also evidenced that the academic formation of the professionals, either the coordinator or the trainer is not an impediment to the development of a multidisciplinary training.
The continued training of the pedagogical coordinator and the training work with the specialist teachers
Keywords: Formação continuada multidisciplinar; Coordenador Pedagógico; Formação de formador; Professor especialista; Continuous multidisciplinary training; Pedagogical coordinator; Specialist teacher; CIENCIAS HUMANAS::EDUCACAO